Conceptualising production, productivity and technology in pharmacy practice: a novel framework for policy, education and research - D Baines; I Bates; L Bader; C Hale; P Schneider (BMC, 2018)
Abstract Context and background People and health systems worldwide face serious challenges due to shifting disease demographics, rising population demands and weaknesses in healthcare provision, including capacity shortages and lack of impact of healthcare services. These multiple challenges, linked with the global push to achieve universal health coverage, have made apparent the importance of investing in workforce development to improve population health and economic well-being. In relation to medicines, health systems face challenges in terms of access to needed medicines, optimising medicines use and reducing risk. In 2017, the International Pharmaceutical Federation (FIP) published global policy on workforce development ('the Nanjing Statements') that describe an envisioned future for professional education and training. The documents make clear that expanding the pharmacy workforce benefits patients, and continually improving education and training produces better clinical outcomes. Aims and purpose The opportunities for harnessing new technologies in pharmacy practice have been relatively ignored. This paper presents a conceptual framework for analysing production methods, productivity and technology in pharmacy practice that differentiates between dispensing and pharmaceutical care services. We outline a framework that may be employed to study the relationship between pharmacy practice and productivity, shaped by educational and technological inputs. Method and results The analysis is performed from the point of view of health systems economics. In relation to pharmaceutical care (patient-oriented practice), pharmacists are service providers; however, their primary purpose is not to deliver consultations, but to maximise the quantum of health gain they secure. Our analysis demonstrates that 'technology shock' is clearly beneficial compared with orthodox notions of productivity or incremental gain implementations. Additionally, the whole process of providing professional services using 'pharmaceutical care technologies' is governed by local institutional frames, suggesting that activities may be structured differently in different places and countries. Discussion and Conclusion Addressing problems with medication use with the development of a pharmaceutical workforce that is sufficient in quantity and competence is a long-term issue. As a result of this analysis, there emerges a challenge about the profession's relationship with existing and emerging technical innovations. Our novel framework is designed to facilitate policy, education and research by providing an analytical approach to service delivery. By using this approach, the profession could develop examples of good practice in both developed and developing countries worldwide.